Aggrecan-like biomimetic proteoglycans (BPGs) composed of natural chondroitin sulfate bristles grafted onto a poly(acrylic acid) core for molecular engineering of the extracellular matrix. (15th July 2018) - Prudnikova, K.; Lightfoot Vidal, S.E.; Sarkar, S.; Yu, T.; Yucha, R.W.; Ganesh, N.; Penn, L.S.; Han, L.; Schauer, C.L.; Vresilovic, E.J.; Marcolongo, M.S.
Graphical abstract: Abstract: Biomimetic proteoglycans (BPGs) were designed to mimic the three-dimensional (3D) bottlebrush architecture of natural extracellular matrix (ECM) proteoglycans, such as aggrecan. BPGs were synthesized by grafting native chondroitin sulfate bristles onto a synthetic poly(acrylic acid) core to form BPGs at a molecular weight of approximately ∼1.6 MDa. The aggrecan mimics were characterized chemically, physically, and structurally, confirming the 3D bottlebrush architecture as well as a level of water uptake, which is greater than that of the natural proteoglycan, aggrecan. Aggrecan mimics were cytocompatible at physiological concentrations. Fluorescently labeled BPGs were injected into the nucleus pulposus of the intervertebral disc ex vivo and were retained in tissue before and after static loading and equilibrium conditioning. BPGs infiltrated the tissue, distributed and integrated with the ECM on a molecular scale, in the absence of a bolus, thus demonstrating a new molecular approach to tissue repair: molecular matrix engineering. Molecular matrix engineering may compliment or offer an acellular alternative to current regenerative medicine strategies. Statement of Significance: Aggrecan is a natural biomolecule that is essential for connective tissue hydration and mechanics. Aggrecan is composed of negatively charged chondroitin sulfate bristles attached to a protein core in a bottlebrush configuration. With age and degeneration, enzymatic degradation of aggrecan outpaces cellular synthesis resulting in a loss of this important molecule. We demonstrate a novel biomimetic molecule composed of natural chondroitin sulfate bristles grafted onto an enzymatically-resistant synthetic core. Our molecule mimics a 3D architecture and charge density of the natural aggrecan, can be delivered via a simple injection and is retained in tissue after equilibrium conditioning and loading. This novel material can serve as a platform for molecular repair, drug delivery and tissue engineering in regenerative medicine approaches.